1970
DOI: 10.1084/jem.132.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Basophil Hypersensitivity

Abstract: Delayed (cell-mediated) hypersensitivity reactions have been regarded by most workers as a qualitatively homogeneous group (1-3), although well-recognized quantitative differences occur depending primarily on mode of immunization. Classic tuberculin-type delayed hypersensitivity is typically produced by the injection of antigen in complete Freund's adjuvant or in other mixtures containing products of the tubercle bacillus; similar reactivity occurs after dermal contact with simple chemicals and after infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Further studies witl be necessary" to determine whether other examples of cell mediated hypersensitivity in man, such as allograft rejection and viral and tumor immunity, have a similar morphology. In any event, our data provide additional support for the hypothesis that "cellular immunity" is composed of a heterogeneous group of reactions mediated by lymphocytes which, while morphologically identical by present methods, are functionally disparate (2,8,9). The presence of basophils in certain of these reactions provides further evidence for the cooperation between lymphocytes (presumably of thymus origin) and bone marrow cells and suggests the possibility of a heretofore unsuspected form of synergism between cellular immunity and the forms of immediate hypersensitivity mediated by homocytotrophic antibody which is bound to the basophil surface (27).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Further studies witl be necessary" to determine whether other examples of cell mediated hypersensitivity in man, such as allograft rejection and viral and tumor immunity, have a similar morphology. In any event, our data provide additional support for the hypothesis that "cellular immunity" is composed of a heterogeneous group of reactions mediated by lymphocytes which, while morphologically identical by present methods, are functionally disparate (2,8,9). The presence of basophils in certain of these reactions provides further evidence for the cooperation between lymphocytes (presumably of thymus origin) and bone marrow cells and suggests the possibility of a heretofore unsuspected form of synergism between cellular immunity and the forms of immediate hypersensitivity mediated by homocytotrophic antibody which is bound to the basophil surface (27).…”
Section: Discussionsupporting
confidence: 66%
“…The sequential arrival of lymphocytes and basophils is consistent with the hypothesis that interaction of sensitized lymphocytes with antigen at a local test site is responsible for the attraction of basophils. This mechanism was proposed in animal studies of CBH reactions which could be passively transferred with lymph node cells and which were inhibited by antilymphocyte serum (3,5,8). In guinea pigs, however, the skin reactions of CBH evolved too rapidly to ascertain that lymphocytes invariably preceded basophils at the local test site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed sensitivity reactions elicited by administration of protein determinants in IFA or in saline have been referred to as cutaneous basophil hypersensitivity or Jones-Mote reactions and have been characterized by the presence of a larger number of basophils in the infiltrate than in the classical tuberculin-type reaction (15) . However, we have considered that both types of reactions are manifestations of the general phenomenon of delayed hypersensitivity whereby inflammatory reactions are elicited by products of sensitized T cells reacting with antigen.…”
Section: Failure Of Aba-specific Suppressor Cells To Inhibit T-cell Rmentioning
confidence: 99%
“…The appearance of the sections confirmed the gross clinical impression of an immediate reaction for it contained numerous polymorphonuclear cells even in sections taken at 24 h. Interestingly, many appeared to be eosinophils rather than neutrophils. The sections also showed that lymphocytes and macrophages had collected about the blood vessels and in the epidermis, in the pattern so characteristic of delayed reactions and of cutaneous basophilic hypersensitivity (16,17,(20)(21)(22)(23). Because prolonged chronic basophilic skin reactions may be confused clinically and histologically with delayed reactions unless a search for basophils is made, sections of 24-h lesions were prepared and examined in 1-fern Epon-embedded sections.…”
Section: Discussionmentioning
confidence: 99%